Optical Glass

By optimizing the content of TiO2 and Nb2O5 in optical glass and adding B2O3 to control basicity, the instability of existing optical glass in terms of refractive index and chemical corrosion resistance is solved, and the effects of high refractive index and excellent chemical corrosion resistance are achieved.

JP7662985B2Active Publication Date: 2025-04-16NIPPON ELECTRIC GLASS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020211971
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-24
Filing Date
2020-12-22
Publication Date
2025-04-16
Estimated Expiration
2040-12-22

AI Technical Summary

Technical Problem

Existing optical glasses have problems with unstable melt temperature and reduced chemical corrosion resistance in improving refractive index and chemical corrosion resistance.

Method used

By optimizing the content of TiO2 and Nb2O5 and adding B2O3 to the glass, the basicity of the glass is controlled within the range of 11 or above to improve the chemical corrosion resistance and refractive index of the glass.

Benefits of technology

It realizes the high refractive index and excellent chemical corrosion resistance of optical glass, ensures the stability and reliability of glass, and is suitable for wearable image display equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662985000001
    Figure 0007662985000001
  • Figure 0007662985000002
    Figure 0007662985000002
Patent Text Reader

Abstract

To provide optical glass containing TiO2 or Nb2O5 and B2O3 as glass composition, having high refractive index and excellent chemical resistance.SOLUTION: Optical glass characterized by a glass composition comprising at least one selected from TiO2 and Nb2O5 and B2O3, having a refractive index nd of 1.95 or larger, and a basicity of 11 or larger.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optical glass used as a light guide plate or the like in a wearable image display device. [Background technology]

[0002] Glass plates are used as components of wearable image display devices such as glasses with projectors, eyeglasses-type or goggle-type displays, virtual reality (VR) or augmented reality (AR) displays, and virtual image displays. The glass plate functions, for example, as a see-through light guide plate, and allows a user to view the image displayed on the glass plate while looking at the outside scenery through the glass plate. It is also possible to realize a 3D display by using a technology to project different images on the left and right sides of the glasses, or to realize a virtual reality space by using a technology to connect the crystalline lens of the eye to the retina. The glass plate is required to have a high refractive index in terms of widening the angle of the image, increasing the brightness and contrast, improving the light guide properties, etc. (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2017-32673 A Summary of the Invention [Problem to be solved by the invention]

[0004] In order to improve the refractive index of glass, it is effective to add TiO2 or Nb2O5, which are components that contribute to a high refractive index, to the glass. However, adding TiO2 or Nb2O5 to glass can lower the liquidus temperature and make vitrification unstable. Therefore, adding B2O3 to glass to stabilize vitrification is an option. However, adding B2O3 to glass can cause a problem of reduced chemical durability.

[0005] In view of the above, an object of the present invention is to provide an optical glass that contains B2O3 in addition to TiO2 and Nb2O5 in its glass composition and has a high refractive index and excellent chemical durability. [Means for solving the problem]

[0006] As a result of extensive investigations, the present inventors have found that the above-mentioned problems can be solved by specifying the basicity, which is an index showing the state of non-bridging oxygen (NBO) in optical glass containing B2O3 in addition to TiO2 and Nb2O5, within a predetermined range.

[0007] That is, the optical glass of the present invention is characterized in that it contains at least one selected from TiO2 and Nb2O5, and B2O3 as a glass composition, has a refractive index nd of 1.95 or more, and a basicity of 11 or more.

[0008] The optical glass of the present invention has a coloring degree λ 70 In the present invention, the coloring degree λ 70 " means the wavelength at which the light transmittance, including reflection losses, is 70% at a thickness of 10 mm.

[0009] The optical glass of the present invention preferably has water resistance and acid resistance of grade 1 or 2 according to JOGIS.

[0010] The optical glass of the present invention preferably contains, in mass %, 10-31% TiO2+Nb2O5, 4-15% B2O3, 3% or more SiO2, 0-15% RO (R is at least one selected from Mg, Ca, Sr and Ba), and 50-5% Ta2O.

[0011] The optical glass of the present invention preferably contains, in mass %, 8 to less than 20% TiO2, 40 to 65% Ln2O3 (Ln is at least one selected from La, Gd, Y and Yb), 0 to 0.5% ZnO, 0 to 1% Al2O3, and 0 to 0.2% WO3.

[0012] The optical glass of the present invention preferably contains substantially no Bi2O3, TeO2, or PbO.

[0013] The optical glass of the present invention preferably has a Pt content of 10 ppm or less.

[0014] The optical glass of the present invention preferably has an Abbe number (νd) of 20-35.

[0015] The optical glass of the present invention preferably has a liquidus temperature of 1250° C. or lower.

[0016] The optical glass plate of the present invention is characterized by being made of the above-mentioned optical glass.

[0017] The optical glass plate of the present invention preferably has a plate thickness of 0.01 to 5 mm.

[0018] The light guide plate of the present invention is characterized by comprising the above-mentioned optical glass plate.

[0019] The light guide plate of the present invention is preferably used in a wearable image display device selected from glasses with a projector, a glasses-type or goggle-type display, a virtual reality (VR) or augmented reality (AR) display device, and a virtual image display device.

[0020] A wearable image display device of the present invention is characterized by including the above-mentioned light guide plate. Effect of the Invention

[0021] According to the present invention, it is possible to provide an optical glass which contains B2O3 as well as TiO2 and Nb2O5 in the glass composition and has a high refractive index and excellent chemical durability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The optical glass of the present invention contains at least one selected from TiO2 and Nb2O5, and B2O3 as a glass composition. The preferred contents of these components are described below. In the following description of the contents of each component, "%" means "mass %" unless otherwise specified.

[0023] TiO2 and Nb2O5 are components that significantly increase the refractive index of glass. They also have the effect of improving chemical durability. However, if these components are too much, the transmittance in the visible range may decrease and vitrification may become difficult. Therefore, the lower limit of the content of TiO2 + Nb2O5 is preferably 10% or more, 11% or more, 12% or more, 14% or more, and particularly 16% or more, and the upper limit is particularly preferably 31% or less, 29% or less, 25% or less, and particularly preferably 20% or less. The lower limit of the content of TiO2 is preferably 8% or more, 9% or more, 11% or more, and particularly preferably 12% or more, and the lower limit is preferably less than 20%, 18% or less, 17% or less, and particularly preferably 16% or less. The lower limit of the Nb2O5 content is preferably 1% or more, 1.7% or more, 2% or more, 2.5% or more, 3.3 or more, 4.4 or more, 5.3 or more, and particularly preferably 6.1 or more, and the upper limit is preferably 25% or less, 22% or less, 20% or less, 18% or less, 15% or less, 14% or less, 10% or less, and particularly preferably 9% or less. In the present invention, "x+y+..." means the total amount of each component.

[0024] In the present invention, in order to obtain a glass having a high refractive index and excellent transmittance in the visible region, it is preferable to appropriately adjust the ratio of TiO2 to Nb2O5. Specifically, it is preferable that the mass ratio of TiO2 / Nb2O5 is 0.3 or more, 0.5 or more, 0.8 or more, and particularly 1 or more. There is no particular upper limit, but in reality it is 29 or less, 20 or less, or even 10 or less.

[0025] B2O3 is a component that contributes to the stability of vitrification in particular in glasses containing TiO2 or Nb2O5. The lower limit of the content of B2O3 is preferably 4% or more, 5% or more, 6.5% or more, 7% or more, 7.5% or more, 8% or more, 8.3% or more, and particularly 9% or more, and the upper limit is preferably 15% or less, 13% or less, 12% or less, 11.5% or less, 11% or less, 10.5% or less, and particularly less than 10.5%. If the content of B2O3 is too low, it is difficult to obtain the above effects. On the other hand, if the content of B2O3 is too high, the refractive index tends to decrease. In addition to containing B2O3, the basicity of the glass is set to 11 or more, thereby improving chemical durability, particularly acid resistance.

[0026] The optical glass of the present invention may contain the following components in addition to TiO2, Nb2O5, and B2O3.

[0027] SiO2 is a glass skeleton component, and is a component that improves the stability of vitrification and chemical durability. However, if the content is too high, the melting temperature becomes extremely high. As a result, Nb and Ti are easily reduced, and the internal transmittance is easily reduced. In addition, the refractive index tends to decrease. The lower limit of the SiO2 content is preferably 3% or more, 3.5% or more, 4% or more, and particularly 4.5% or more, and the upper limit is preferably 20% or less, 18% or less, 15% or less, 13% or less, 12% or less, 11% or less, 10% or less, 9% or less, and particularly 8% or less.

[0028] The alkaline earth component RO (R is at least one selected from Ca, Sr, and Ba) is a component that stabilizes vitrification. If the content is too high, the refractive index tends to decrease and the liquidus temperature tends to increase. In particular, with regard to BaO, if the content is high, the density of the glass increases, and the weight of the optical element made of the optical glass of the present invention tends to increase. Therefore, it is not preferable for use in wearable image display devices and the like. Therefore, the content of RO is preferably 0 to 15%, 0 to 10%, 0 to 5%, 0 to 2%, 0 to 1%, and particularly 0 to 0.5%. The preferred ranges of the contents of each of the CaO, SrO, and BaO components are also preferably the same as above.

[0029] Ta2O5 is a component that increases the refractive index. However, if the content is too high, phase separation and devitrification are likely to occur. In addition, since Ta2O5 is a rare and expensive component, if the content is high, the raw material batch cost will increase. In view of the above, the content of Ta2O5 is preferably 0 to 5%, 0 to 3%, or 0 to 1%, and it is particularly preferable that it is not contained.

[0030] In order to increase the stability of vitrification and improve mass productivity, it is preferable to appropriately adjust the ratio of SiO2 to B2O3. Specifically, the mass ratio of B2O3 / SiO2 is preferably 1 or more, 1.3 or more, and particularly 1.5 or more, and is preferably 2.5 or less, 2 or less, and particularly 1.96 or less. In the present invention, "x / y" means the value obtained by dividing the content of x by the content of y.

[0031] Al2O3 is a component that improves water resistance. However, if the content is too high, the glass is likely to become devitrified. Therefore, the content of Al2O3 is preferably 0 to 1%, 0 to 0.5%, and it is particularly preferable that it is not contained.

[0032] La2O3 is a component that significantly increases the refractive index and improves the stability of vitrification. The lower limit of the La2O3 content is preferably 27% or more, 30% or more, 35% or more, 38% or more, 40% or more, 42% or more, and particularly 45% or more, and the upper limit is preferably 50% or less, 49.8% or less, 49.5% or less, 49% or less, and particularly 48.5% or less. If the La2O3 content is too low, it is difficult to obtain the above effects. On the other hand, if the La2O3 content is too high, the devitrification resistance decreases and mass productivity tends to be poor.

[0033] Gd2O3 is also a component that increases the refractive index and improves the stability of vitrification. The lower limit of the Gd2O3 content is preferably 6% or more, particularly 6.5% or more, and the upper limit is preferably 25% or less, 20% or less, 14% or less, 10% or less, particularly 9% or less.

[0034] Y2O3 is also a component that increases the refractive index, but if its content is too high, vitrification tends to become unstable. Therefore, the lower limit of the Y2O3 content is preferably 0% or more, particularly 0.1% or more, and the upper limit is preferably 8% or less, 5% or less, 3% or less, particularly less than 1%.

[0035] Yb2O3 is also a component that increases the refractive index. However, if the content is too high, devitrification and striae tend to occur. Therefore, the content of Yb2O3 is preferably 0 to 10%, and more preferably 0 to 8%.

[0036] The content of Ln2O3 (wherein Ln is at least one selected from La, Gd, Y, and Yb) is preferably 40% or more, 45% or more, and particularly preferably 48% or more. This makes it possible to increase the refractive index and light transmittance in the visible range. There is no particular upper limit to the content of Ln2O3, but if it is too high, devitrification is likely to occur, so it is preferably 65% ​​or less, and particularly preferably 60% or less.

[0037] In the composition of the present invention, ZnO is a component that promotes devitrification and reduces acid resistance, and therefore its content is preferably small. Specifically, the ZnO content is preferably 0.5% or less, more preferably 0.1% or less, and particularly preferably zero.

[0038] WO3 is a component that increases the refractive index, but absorbs light in the visible region and reduces the transmittance. The content of WO3 is preferably 0 to 0.2%, more preferably 0 to 0.1%, and particularly preferably zero.

[0039] ZrO2 is a component that enhances the refractive index and chemical durability. The lower limit of the ZrO2 content is preferably 0% or more, more than 0%, 1% or more, 3% or more, 4% or more, and particularly preferably 5% or more, and the upper limit is preferably 10% or less, 9% or less, 8% or less, 7.5% or less, and particularly preferably 7% or less. If the ZrO2 content is too high, devitrification is likely to occur.

[0040] Li2O, Na2O, and K2O are components that lower the softening point, but if the content is too high, devitrification will occur easily. Therefore, the content of these components is preferably 0 to 3%, and 0 to 1%, respectively, and it is particularly preferable that they are not contained.

[0041] In the present invention, in order to obtain a glass having a high refractive index and excellent vitrification stability, it is preferable to appropriately adjust the total amount of SiO2 and B2O3 and the ratio of Ln2O3. Specifically, the lower limit of (SiO2+B2O3) / Ln2O3 is preferably 0.15 or more, 0.2 or more, and particularly preferably 0.25 or more, and the upper limit is preferably 0.9 or less, 0.6 or less, and particularly preferably 0.5 or less.

[0042] In the present invention, in order to obtain a glass having a high refractive index and excellent transmittance in the visible range, it is preferable to appropriately adjust the ratios of TiO2, Nb2O5, and ZrO2. Specifically, the lower limit of the mass ratio of Nb2O5 / (TiO2+Nb2O5+ZrO2) is preferably 0.1 or more, 0.15 or more, and particularly preferably 0.2 or more, and the upper limit is preferably 0.46 or less, 0.4 or less, and particularly preferably 0.37 or less.

[0043] In the present invention, in order to obtain a glass having excellent transmittance in the visible region, it is preferable to appropriately adjust the total amount of TiO2, Nb2O5, and WO3. Specifically, the content of TiO2+Nb2O5+WO3 is preferably 31% or less, 29% or less, 25% or less, and particularly preferably 20% or less. However, if the content of these components is too small, it becomes difficult to obtain the desired high refractive index characteristics, so the lower limit of the content of TiO2+Nb2O5+WO3 is preferably 10% or more, 11% or more, and particularly preferably 12% or more.

[0044] In the present invention, in order to obtain a glass having a high refractive index and excellent transmittance in the visible range, it is preferable to appropriately adjust the ratios of TiO2, Nb2O5, and WO3. Specifically, the lower limit of the mass ratio of Nb2O5 / (TiO2+Nb2O5+WO3) is preferably 0.15 or more, 0.2 or more, and particularly preferably 0.3 or more, and the upper limit is preferably 0.8 or less, 0.6 or less, and particularly preferably 0.5 or less.

[0045] In the present invention, in order to increase the refractive index and the light transmittance in the visible region and to improve the stability of vitrification, it is preferable to appropriately adjust the ratio of Y2O3 and Ln2O3. Specifically, the lower limit of Y2O3 / Ln2O3 is preferably 0 or more, 0.005 or more, and particularly preferably 0.01 or more, and the upper limit is preferably 0.1 or less, 0.05 or less, and particularly preferably 0.3 or less.

[0046] In the present invention, in order to increase the refractive index and the light transmittance in the visible region and to improve the stability of vitrification, it is preferable to appropriately adjust the ratio of Gd2O3 and Ln2O3. Specifically, the lower limit of Gd2O3 / Ln2O3 is preferably 0.1 or more, particularly 0.12 or more, and the upper limit is preferably 0.25 or less, particularly 0.2 or less.

[0047] In the present invention, in order to increase the refractive index and the light transmittance in the visible region and to improve the stability of vitrification, it is preferable to appropriately adjust the ratio of the total amount of TiO2 and B2O3 to the total amount of Nb2O5 and WO3. Specifically, the lower limit of (TiO2+B2O3) / (Nb2O5+WO3) is preferably 1.6 or more, 1.8 or more, and particularly preferably 2 or more, and the upper limit is preferably 10 or less, 4 or less, and particularly preferably 3.5 or less.

[0048] In addition, it is preferable that As components (As2O3, etc.), Pb components (PbO, etc.), and fluorine components (F2, etc.) are not substantially contained because they have a large environmental impact. In addition, Bi2O3 and TeO2 are coloring components, and they tend to reduce the transmittance in the visible range, so it is preferable that they are not substantially contained. Note that "substantially not contained" here means that they are not intentionally contained as raw materials, and does not exclude the inclusion of unavoidable impurities. Objectively, it means that the content of each of the above components is less than 0.1%.

[0049] Pt is a coloring component that tends to reduce transmittance in the visible range, so the content is preferably 10 ppm or less.

[0050] The optical glass of the present invention may contain fining agents Cl, CeO2, SO2, Sb2O3, or SnO2 in proportions of 0.1% or less each.

[0051] The optical glass of the present invention has a glass basicity defined as (sum of moles of oxygen atoms / sum of field strengths of cations) x 100 of at least 11, preferably at least 12, and more preferably at least 12.5. In the present invention, the "field strength (hereinafter abbreviated as FS)" is calculated by the following formula:

[0052] FS=Z / r 2 (Z is the ionic valence and r is the ionic radius (Å).

[0053] In the present invention, the values ​​of Z and r are those in Table 1. For r, the values ​​listed in "Chemical Handbook, Basic Edition, Revised 2nd Edition (published by Maruzen Co., Ltd. in 1975)" and the like are used. However, B 3+ and P 5+ The ionic radius of B is a tetrahedral structure with oxygen ions in the glass (specifically, B 3+ or P 5+ With four O's around it 2- The value is set to 0.32, assuming that the ions are coordinated to form a tetrahedral structure.

[0054] [Table 1]

[0055] Basicity is an index showing the state of electron or oxygen binding by cations. The higher the basicity, the weaker the binding of electrons or oxygen by cations. Oxygen is easily arranged around boron element, which has low chemical durability, and boron is stable in glass, so that chemical durability is easily improved. If the binding of electrons or oxygen by cations becomes too weak, vitrification becomes unstable and, conversely, chemical durability tends to decrease, so the basicity is preferably 17 or less, 16 or less, and particularly 15 or less.

[0056] In addition, when the binding of electrons or oxygen by cations becomes weak, Ti ions and Nb ions tend to be oxidized, and Ti ions do not decrease the visible light transmittance. 4+ Or Nb 5+ This makes it possible to improve the visible light transmittance of the optical glass of the present invention.

[0057] The lower limit of the refractive index (nd) of the optical glass of the present invention is 1.95 or more, preferably 1.96 or more, 1.965 or more, 1.966 or more, 1.97 or more, particularly 1.98 or more, and the upper limit is preferably 2.05 or less, 2.04 or less, 2.03 or less, 2.01 or less, particularly 2.00 or less. If the refractive index is too low, the viewing angle tends to be narrow when used as a light guide plate for wearable image display devices such as glasses with projectors, eyeglass-type or goggle-type displays, virtual reality (VR) or augmented reality (AR) displays, and virtual image displays. On the other hand, if the refractive index is too high, the glass is more likely to have defects such as devitrification and striae.

[0058] Coloring degree λ of the optical glass of the present invention 70 It is preferable that the wavelength is 470 nm or less, and particularly 460 nm or less. In this way, in a wearable image display device using the optical glass of the present invention, the brightness of the image seen by the user tends to be increased.

[0059] The Abbe number (νd) of the optical glass of the present invention is not particularly limited, but in consideration of the stability of vitrification, the lower limit is preferably 20 or more, more preferably 22 or more, and even more preferably 25 or more, and the upper limit is preferably 35 or less. , 32 or less, particularly preferably 30 or less.

[0060] The liquidus temperature of the optical glass of the present invention is preferably not higher than 1250° C., not higher than 1200° C., not higher than 1150° C., not higher than 1100° C., and particularly preferably not higher than 1070° C. In this way, the glass is less susceptible to devitrification during melting or molding, which tends to improve mass productivity.

[0061] The optical glass of the present invention has a density of 5.5 g / cm 3 Below, 5.3g / cm 3 Below, especially 5.1g / cm 3 If the density is too high, the weight of a wearable device using the optical glass of the present invention increases, increasing the discomfort felt when wearing the device. There is no particular lower limit to the density, but if it is too low, other properties such as optical properties decrease, so a lower limit of 4.0 g / cm is preferred. 3 Above, especially 4.5g / cm3 More preferably, it is equal to or greater than this.

[0062] The optical glass of the present invention has a thermal expansion coefficient of 95×10 -7 / ℃ or less, 91×10 -7 / ℃ or less, especially 88×10 -7 / °C or less. If the thermal expansion coefficient is too high, the glass is likely to break due to thermal shock. There is no particular lower limit for the thermal expansion coefficient, but if it is too low, other properties such as optical properties are reduced. -7 / ℃ or higher, especially 80×10 -7 It is preferable that the temperature is 100° C. or higher.

[0063] The lower limit of the thickness of the optical glass plate made of the optical glass of the present invention is preferably 0.01 mm or more, 0.02 mm or more, 0.03 mm or more, 0.04 mm or more, particularly 0.05 mm or more, and the upper limit is preferably 5 mm or less, 3 mm or less, 1 mm or less, 0.8 mm or less, 0.6 mm or less, particularly 0.3 mm or less. If the thickness of the optical glass plate is too small, the mechanical strength is likely to decrease. On the other hand, if the thickness of the optical glass plate is too large, the weight of the wearable image display device using the optical glass plate increases, and the discomfort when wearing the device increases.

[0064] The shape of the optical glass plate of the present invention is, for example, a plate shape having a planar shape of a circle, an ellipse, or a polygon such as a rectangle. In this case, the major axis of the optical glass plate (diameter in the case of a circle) is preferably 50 mm or more, 80 mm or more, 100 mm or more, 120 mm or more, 150 mm or more, 160 mm or more, 170 mm or more, 180 mm or more, 190 mm or more, and particularly 200 mm or more. If the major axis of the optical glass plate is too small, it becomes difficult to use it for applications such as wearable image display devices. In addition, mass productivity tends to be poor. The upper limit of the major axis of the optical glass plate is not particularly limited, but in reality it is 1000 mm or less.

[0065] The optical glass plate of the present invention is suitable as a light guide plate that is a component of a wearable image display device selected from glasses with a projector, a glasses-type or goggle-type display, a virtual reality (VR) or augmented reality (AR) display device, and a virtual image display device. The light guide plate is used in the so-called glasses lens portion of the wearable image display device, and serves to guide light emitted from an image display element included in the wearable image display device and emit the light toward the user's pupil. It is preferable that a diffraction grating is provided on the surface of the light guide plate for diffracting the light emitted from the image display element into the light guide plate. EXAMPLES

[0066] The present invention will be described in detail below using examples, but the present invention is not limited to these examples.

[0067] Table 2 shows examples (Nos. 1 to 9) of the present invention and a comparative example (No. 10).

[0068] [Table 2]

[0069] First, glass raw materials were mixed to obtain the compositions shown in Table 2, and melted in a platinum crucible at 1200 to 1350°C for 2 hours. The molten glass was poured onto a carbon plate and further annealed to prepare samples suitable for each measurement.

[0070] The obtained samples were evaluated for Pt content, water resistance, acid resistance, and coloring degree λ 70 The liquidus temperature, liquidus viscosity, refractive index (nd), Abbe number (νd), density, and thermal expansion coefficient were measured. The results are shown in Table 2.

[0071] The Pt content was measured by ICP mass spectrometry after decomposing the crushed glass samples with a mixed acid containing HF, HCLO4, HNO3 and HCl.

[0072] The water resistance and acid resistance were measured based on the powder method specified in JOGIS.

[0073] Coloring degree λ 70 was measured as follows. For an optically polished sample with a thickness of 10 mm±0.1 mm, the light transmittance (linear transmittance) including the surface reflection loss was measured at 0.5 nm intervals using a spectrophotometer (Shimadzu Corporation UV-3100). The wavelength at which the light transmittance was 70% was read from the light transmittance curve obtained by the measurement.

[0074] The liquidus temperature and liquidus viscosity were measured as follows.

[0075] The glass was remelted in an electric furnace at 1200°C for 0.5 hours, then held in an electric furnace with a temperature gradient for 18 hours, after which it was removed from the furnace and allowed to cool in air. Measurements were then performed by determining the positions of devitrified matter using an optical microscope.

[0076] Separately, a lump glass sample was placed in an alumina crucible and heated to melt. The viscosity of the resulting molten glass was measured at a number of temperatures using the platinum ball pulling method. Next, the measured values ​​of the glass viscosity were used to calculate the constants of the Vogel-Fulcher equation to create a viscosity curve.

[0077] Using the liquidus temperature and viscosity curve thus determined, the viscosity corresponding to the liquidus temperature (liquidus viscosity) was determined.

[0078] The refractive index is shown as a measurement value for the d line (587.6 nm) of a helium lamp. The Abbe number was calculated from the Abbe number (νd) = [(nd-1) / (nF-nC)] using the refractive index of the d line, the F line (486.1 nm) of a hydrogen lamp, and the C line (656.3 nm) of a hydrogen lamp.

[0079] The density was measured by Archimedes' method using a glass sample weighing about 10 g.

[0080] The thermal expansion coefficient was measured in the temperature range of 30 to 300°C using a dilatometer using a glass sample molded to approximately 5φ×20 mm.

[0081] As shown in Table 2, the samples No. 1 to No. 9, which are examples, had a basicity of 11.6 to 17, and both water resistance and acid resistance were Class 1. The refractive index was also high, ranging from 1.952 to 2.04. On the other hand, the sample No. 10, which is a comparative example, had a basicity of 9.3, a poor acid resistance of Class 4, and a low refractive index of 1.81. [Industrial Applicability]

[0082] The optical glass of the present invention is suitable as a light guide plate for use in a wearable image display device selected from glasses with a projector, a glasses-type or goggle-type display, a virtual reality (VR) or augmented reality (AR) display device, and a virtual image display device.

Claims

1. Glass composition: TiO 2 and Nb 2 O 5 At least one selected from and B 2 O 3 Contains, in mass%, La 2 O 3 35-46.9%, TiO2 11-less than 20%, Nb 2 O 5 1-7.6%, Gd 2 O 3 0-7.9%, WO 3 An optical glass containing 0-0.2% of ZnO and 0.5% or less, having a refractive index nd of 1.95 or more and a basicity of 11 or more.

2. Coloring degree λ 70 2. The optical glass according to claim 1, wherein the optical transmittance is 470 nm or less.

3. 3. The optical glass according to claim 1, wherein the water resistance and acid resistance according to JOGIS are class 1 or 2.

4. In mass%, TiO 2 +Nb 2 O 5 12-25%, B 2 O 3 4-15%, SiO 2 3% or more, RO (R is at least one selected from Mg, Ca, Sr and Ba) 0 to 15%, and Ta 2 O 5 4. The optical glass according to claim 1, wherein the content is 0 to 5%.

5. In mass%, Ln 2 O 3 (Ln is at least one selected from La, Gd, Y and Yb) 40 to 65% and Al 2 O 3 5. The optical glass according to claim 4, containing 0 to 1% of ZnO.

6. Bi 2 O 3 , TeO 2 6. The optical glass according to claim 1, which is substantially free of PbO.

7. 7. The optical glass according to claim 1, wherein the Pt content is 10 ppm or less.

8. 8. The optical glass according to claim 1, wherein the Abbe number (νd) is 20-35.

9. 9. The optical glass according to claim 1, wherein the liquidus temperature is 1250° C. or lower.

10. An optical glass plate comprising the optical glass according to any one of claims 1 to 9.

11. 11. The optical glass plate according to claim 10, wherein the plate thickness is 0.01 to 5 mm.

12. A light guide plate comprising the optical glass plate according to claim 10 or 11.

13. The light guide plate according to claim 12, which is used in a wearable image display device selected from glasses with a projector, a glasses-type or goggle-type display, a virtual reality (VR) or augmented reality (AR) display device, and a virtual image display device.

14. A wearable image display device comprising the light guide plate according to claim 12 or 13.

Citation Information

Patent Citations

  • Optical glass having high refractive index

    JP1985033229A

  • Optical glass, preform, and optical element

    JP2012162448A

  • Optical glass

    JP2013253013A

  • Optical glass and optical element

    JP2014221704A

  • Optical glass

    JP2015020913A